(untitled) (Economics and region, 2023)
Currently, given the scale and types of activities, changes in legislation and the development of information technology, companies have different requirements for accounting and financial reporting. In this regard, the development of an effective accounting policy is a key factor in ensuring the successful operation of the company. The following issues remain unresolved in the scientific interpretation of accounting policies: peculiarities of developing accounting policies for different organisational and legal forms and sizes of business entities, the purpose of accounting policies for management accounting purposes, a clear list and specification of the stages of document development, the availability of a unified system for modelling accounting policies that could be used by those developing such a document, and the use of information technology to improve decision-making at various levels. The aim of the study is to improve the theoretical, methodological and organisational support of the process of formation of the accounting policy of enterprises and its legal support. The set of tasks aimed at achieving this goal is as follows: - Research and disclosure of the definition of accounting policy and its legal support; - list of possible factors that influence the process of creating an Accounting Policy Order; - study of information support for accounting policy by existing types of accounting; - disclosure of accounting policies as a factor influencing the formation of financial results of any business; - determination of the impact of accounting policies on the financial performance of the company; - provision of recommendations for improving accounting policies to enhance enterprise management. The study is based on the dialectical method, which provides for the disclosure of the essence of accounting policy, its tasks and functions. Depending on the nature of the task under study, the study used general scientific techniques and methods, such as the comprehensive method, which was used to collect, analyse and summarise information on the study of literary and legislative sources; synthesis, which allows combining and summarising the definitions of accounting policies that reveal their main content; tabular method, which was used to create tables containing numerical data, textual descriptions or a combination of both; modelling method, which was used to improve management. The scientific novelty of the obtained results lies in improvement of the theoretical, methodological and organisational foundations of the accounting policy of an economic entity and relevant recommendations for its formation and use. The obtained results of the study are to implement in practice the proposals for improving the methodology of accounting policy formation, its organisation and legal support.